PERAN STRATEGIS FILSAFAT ISLAM DALAM PENGEMBANGAN KAJIAN PSIKOLOGI ISLAM - Muhammad Zainal Abidin (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2009)
This article tries to explore the strategic role of Islamicphilosophy in developing psychological studies. There are two ways todevelop psychological studies. First, studies based on Islamic tradition,and second studies based on modern psychology. The former is usuallycalled “Islamic psychology” which is based on traditional Islamicknowledge like Islamic philosophy and Sufism, while the latter is called“psychology of Islam” which is based on certain elements of modernpsychology considered in line with Islamic values. In fact, both kinds ofpsychological studies are important if we want to put Islam andpsychology together.